2014
DOI: 10.2169/internalmedicine.53.1277
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Indicators are Correlated with the Radiological Severity Score in Patients with <i>Mycobacterium avium</i> Complex Pulmonary Disease: A Cross-sectional Study

Abstract: Objective Body weight loss in patients with Mycobacterium avium complex (MAC) pulmonary disease can be fatal. The administration of nutritional supplements should be an important component in the treatment of this disease. Objective data regarding the association between the nutritional status and disease severity have not been reported. This cross-sectional study aimed to compare the nutritional status and radiological severity scores in MAC pulmonary disease patients. Methods We retrospectively reviewed the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…Preoperative chest CT images of all patients were acquired within a month before surgery and evaluated by two pulmonologists blinded to the clinical data. To assess radiological severity, we used the National Institute for Health and Care Excellence scoring method (NICE score) [22]. The NICE score was calculated as below.…”
Section: Data Collectionmentioning
confidence: 99%
“…Preoperative chest CT images of all patients were acquired within a month before surgery and evaluated by two pulmonologists blinded to the clinical data. To assess radiological severity, we used the National Institute for Health and Care Excellence scoring method (NICE score) [22]. The NICE score was calculated as below.…”
Section: Data Collectionmentioning
confidence: 99%
“…Typical characteristics of patients with NTM-PD are low body mass index (BMI) and history of weight loss [30][31][32]. Such features are among those that make the clinician suspect a NTM infection and are so typical of middle-aged women that a specific phenotype called "Lady Windermere syndrome" has been identified [33].…”
Section: Nutritional Evaluation and Interventionmentioning
confidence: 99%
“…Physical deconditioning is frequent in patients with COPD as well as bronchiectasis [ 49 ]; however, the presence of sarcopenia and the evaluation of muscle mass in patients with NTM-PD have only been marginally evaluated. M orimoto et al [ 30 ] described decreased muscle mass in patients with MAC-PD and found that the percentage of triceps skinfold and mid-upper arm muscle circumference were negatively correlated with the severity of radiological scores.…”
Section: Nutritional Evaluation and Interventionmentioning
confidence: 99%
“…47 Nutritional deficiencies may also contribute to the development of LWS since malnutrition is associated with increased risk of M. tuberculosis infection and with worse outcomes in NTM infections. 51,52 Several genetic factors and subtle immune phenotypes are more common in patients with LWS than in the general population. Most notably, 36.5% of patients with pulmonary NTM had one CFTR mutations compared to 15.6% of individuals in the control population.…”
Section: Pathogenesismentioning
confidence: 99%